Fārābī’s Theory of Language and Its Relevance to Contemporary Issues in Universal Grammar and Cognitive Semantics - Asghar, Jamil; Shahzad, Khurram (Islamic Studies, 2020)
Abū Naṣr Muḥammad b. Muḥammad al-Fārābī (d. 339/950), a renowned Muslim philosopher, logician, and a polymath, is relatively lesser known for his contribution to the study of language, and most of his introductions are based on his politico-philosophical writings. The present paper seeks to throw light on Fārābī’s contribution to linguistics and critically compare it with the ideas of some of the most notable contemporary linguists, chiefly with those of Noam Chomsky. The study traces remarkable similarities as well as crucial differences. Fārābī’s Kitāb al-Ḥurūf (Book of Letters) contains many of his ideas, which harbingered some of the most far-reaching linguistic theories/disciplines of the twentieth century, including universal grammar, cognitive semantics, formal semantics, Saussurean structuralism, and discourse studies. Writers and researchers as diverse as Ian R. Netton, Peter Adamson, Muhammad Ali Khalidi, Richard Rudolph Walzer, Thérèse-Anne Druart, Charles Butterworth, and Nadja Germann have played a significant role over the recent years to highlight Fārābī’s accomplishments in the field of linguistics. The present-day language-related issues allow us to appreciate more profitably the singularity of Fārābī as an exceedingly perceptive linguist and a semanticist. This paper too is a contribution to this tradition.